Implementasi Alat Pengering Cabinet Dryer untuk Mengatasi Masalah Pengeringan Kerupuk pada Usaha Kecil Kerupuk - Purnomo Purnomo; Dwi Sulistyaningsih; R. Ery Wibowo A (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Crackers "Sarah" and "Barokah" have decreased cracker production due to, firstly, low speed of chopping because it is still done manually, and second is the failure of drying crackers as a result of the absence of the sun. The purpose of community service is to improve the quantity and quality of cracker production. The method applied is by implementing chopper machine and dryer dryer machine on dry cracker cracker. The results show that the use of chopper machine is able to remind the speed of chopping while improving the quality of the grain. The use of cracker dryer machine can accelerate drying so as to increase the production of crackers.Keywords: chopper machine, drying machine, crackers